Factors that influence refractive errors in premature infants - Surasmiati, Ni Made Ayu; Handayani, Ariesanti Tri; Sutyawan, I Wayan Eka (Universa Medicina, 2024)
Background The prevalence of refractive errors is reported to be higher in children born preterm. Factors such as gestational age, birth weight, and retinopathy of prematurity status, have a significant impact on the refractive development in preterm infants. Prematurity and low birth weight affect the development of organ systems in infants, including the eyes. In addition to immature retinas, other eye conditions, such as refractive status, are also observed. This study aimed to determine the risk factors of refractive status, specifically refractive errors (spherical equivalent, astigmatism, and anisometropia) in premature infants at a tertiary hospital in Bali. MethodsA cross-sectional study was conducted involving 53 premature infants. This study collected samples from January to August 2023 at the Neonatal Intensive Care Unit of Prof. dr. IGNG Ngoerah General Hospital. Data regarding gender, gestational age, birth weight, retinal condition, spherical equivalent, and refractive disorders were collected. The relationship between risk factors and spherical equivalent, astigmatism, and anisometropia were analyzed using multiple regression analysis with statistical significance set at p<0.05. ResultsHypermetropia is the most common finding in premature infants, followed by myopia and astigmatism. The prevalence of myopia (9.4%) and astigmatism (5.7%) is also more common among newborns of gestational age ≤30 weeks (p=0.024). Chronological age was significantly associated with spherical equivalent (β=0.424; p=0.019). ConclusionIn premature infants, chronological age was the risk factor of spherical equivalent. Other risk factors were not associated with the prevalence of refractive errors among premature infants.